English songs and their influence on long-term vocabulary gains in UTAR undergraduates - Chan, Chervon Yen Wen (2022)
Non-native English learners often struggle to retain newly learnt vocabulary. Songs have attributes suitable for vocabulary learning—repetitive and conversation-like—this shows their high potential of being a vocabulary learning tool outside of classrooms. Various past research demonstrate the effectiveness of songs for vocabulary learning and retention in classroom settings, but little study can be found on the impact of songs on vocabulary learning outside of classrooms. It is unclear how listening to English songs and the repetition of these songs will impact the vocabulary gains of ESL undergraduates outside of classrooms. 100 English language and English education undergraduates from Universiti Tunku Abdul Rahman (UTAR), Kampar Campus, Malaysia, were evenly and randomly assigned into short-term and long-term groups. The present study presents several perceptions of undergraduates on English songs and the effects of repetition of songs on long-term vocabulary gains. The results indicated that (a) the perception of undergraduates on English songs could be categorised into the themes of tune and rhythm, English pronunciation, acquisition and retention of vocabulary, accessibility, creates a low-stress environment, and prefer other learning methods, (b) there is little significance between repetition on vocabulary gains, and (c) one-week duration after the listening session posed little significance between repetition and long-term vocabulary gain retention.